Pengembangan Bahan Ajar Menulis Puisi Bermuatan Kebhinekaan Pancasila untuk Mereduksi Radikalisme Siswa SMP - Sri Mulyati; Muryidah Dwi Hartati; Tri Mulyono (Cakrawala: Jurnal Pendidikan, 2018)
The research aimed to develop the teaching material of poetry that was charged with Pancasila's diversity for Junior High School students in Tegal City. Specific teaching materials writing poems were still minimal. Writing poetry was only a matter of outline. Lack of teaching materials caused the ability of students in writing poetry was low. This research used a research and development approach (R & D) conducted with five phases, namely: (1) preliminary survey; (2) the development of prototype teaching materials writing Poems of Pancasila diversity (3) evaluation of teaching materials prototype; (4) repair/revision of teaching material prototype; and (5) Testing the effectiveness of the teaching materials developed. Requirement analysis using questionnaire, while validation of teaching materials prototype using validation test sheet. Collected data were analysed by quantitative descriptive technique. The teaching material of poetry was integrated with the Pancasila diversity value charge as an attempt to reduce the fundamental understanding of Junior High School students in Tegal City. Pancasila's diversity in teaching materials was embedded in the selection of themes and examples of poems presented. Students who read and write poems that are charged with Pancasila's variety are expected to have an understanding of Pancasila's high values. Students who understand the noble values of Pancasila will be able to reduce the radical perception they receive from the media and interactions in the Pancasila environment.